Optimal power flow‐based reactive power control in smart distribution network using real‐time cyber‐physical co‐simulation framework - Raju Wagle; Pawan Sharma; Charu Sharma; Mohammad Amin; Jose Luis Rueda; Francisco Gonzalez‐Longatt (IET Generation, Transmission & Distribution, 2023)
Abstract Future distribution networks (DN) are subject to rapid load changes and high penetration of variable distributed energy resources (DER). Due to this, the DN operators face several operational challenges, especially voltage violations. Optimal power flow (OPF)‐based reactive power control (RPC) from the smart converter (SC) is one of the viable solutions to address such violations. However, sufficient communication and monitoring infrastructures are not available for OPF‐based RPC. With the development of the latest information communication technology in SC, cyber‐physical co‐simulation (CPCS) has been extensively used for real‐time monitoring and control. Moreover, deploying OPF‐based RPC using CPCS considering the controller design of SC for a realistic DN is still a big challenge. Hence, this paper aims to mitigate voltage violations by using OPF‐based RPC in a real‐time CPCS framework with multiple SCs in a realistic DN. The OPF‐based RPC is achieved by performing the CPCS framework developed in this study. The CIGRE medium‐voltage DN is considered as a test system. Real‐time optimization and signal processing are achieved by Python‐based programs using a model‐based toolchain of a real‐time DN solver and simulator. Real‐time simulation studies showed that the proposed method is capable of handling uncertain voltage violations in real time.